Media Scheduling: A Stochastic Dynamic Model Approach - Zufryden, Fred S. (Management Science, 1973)
A stochastic model is developed with application to both the study of consumer behavior and the scheduling of advertising media. This model incorporates a stochastic response behavior model which examines changes in brand purchase probability over time through the integration of consumer advertising exposure response, purchase incidence behavior and purchase-event feedback constructs. The response behavior model provides the basis for the objective function of a general media scheduling model that is formulated as a binary integer mathematical programming system. Among the factors considered or reflected in the media model are the sales potentials of the target audience and respective market segments, advertising budget, media timing, exposure probabilities, and time patterns (e.g., advertising carry-over, forgetting and saturation effects). Finally, efficient heuristic programming techniques are proposed for solving the media model.